Complete mitogenome and phylogenetic analysis of Brassica oleracea L. var. italica Plenck - Xuli Pei; Zange Jing; Muneeb Ahmad Wani; Zheng Tang; Zhenchao Zhang; Qian Xu; Meiqi Tao; Liling Mo; Peng Jiao (Mitochondrial DNA. Part B. Resources)
In this study, we assembled and annotated the mitochondrial genome (mitogenome) of B. oleracea L. var. italica Plenck. This mitogenome was found to span 219 964 bp, with a GC content of 45.25%. It comprised 61 genes, including 35 protein-coding, 23 transfer RNA, and three ribosomal RNA genes. Among these, only 11 genes contained introns. Codon preference analysis revealed a bias toward codons ending in A/U bases. A phylogenetic analysis demonstrated a close relationship between B. oleracea L. var. italica Plenck, B. oleracea L. botrytis, and B. oleracea var. capitata. This reference mitogenome provides a basis for research on genetic conservation, phylogenetic relationships, and molecular breeding strategies among members of the Brassica genus.